Digitalization and resilience enhancement: How digital infrastructure construction affects urban resilience - Bo Lu; Ruyi Shi; Yibao Wang (PLoS ONE, 2025)
Enhancing urban resilience is critical for mitigating disaster risks. This study investigates the relationship between digital infrastructure construction (DIC) and urban resilience using panel data from 283 cities in China (2011–2022). Employing constructed indices for DIC and multi-dimensional urban resilience, we empirically analyze the mechanisms and spatial spillover effects of DIC. The study finds: (1) DIC significantly enhances urban resilience, with this positive effect mediated through improvements in critical public services, technological innovation, and resource allocation efficiency. (2) The resilience-enhancing impact of DIC exhibits significant heterogeneity, varying substantially across regions and industrial structures. (3) DIC generates positive spatial spillovers, boosting urban resilience not only locally but also in neighboring regions. These findings provide robust empirical evidence for leveraging DIC as a strategic tool to strengthen urban resilience against disasters.